1970
DOI: 10.3329/sjps.v3i1.6802
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antioxidant Potential of Different Extracts of <i>Celastrus paniculatus</i> Willd. Seed

Abstract: The objective of the present study was to evaluate the comparative antioxidant potential of methanol, ethyl acetate, pet ether and water extracts of Celastrus paniculatus seed. Antioxidant activity was evaluated by using total phenol and flavonoid content determination assays, total antioxidant capacity, 1,1-diphenyl-2-picryl-hydrazil (DPPH) free radical assay, Reducing power assessment, Nitric oxide (NO) scavenging assay and Cupric ion reducing capacity assay (CUPRAC method). The extracts showed moderate anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…As, higher the absorbance of the extracts more will be the antioxidant activity. Previous studies also reported that the phenolic and flavonoid contents are responsible for antioxidant activity [17][18]. A study reported in 2016, by Sharma and his coworkers showed that methanol extract of the stem and leaves of Callicarpa arborea has an IC 50 value of 53.65 and 47.20 at the concentrations of 100-500µg/ ml, respectively containing phenolic compounds [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As, higher the absorbance of the extracts more will be the antioxidant activity. Previous studies also reported that the phenolic and flavonoid contents are responsible for antioxidant activity [17][18]. A study reported in 2016, by Sharma and his coworkers showed that methanol extract of the stem and leaves of Callicarpa arborea has an IC 50 value of 53.65 and 47.20 at the concentrations of 100-500µg/ ml, respectively containing phenolic compounds [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that Celastrus paniculatus seeds ethyl acetate extract was IC 50 value of 558.58 and 601.81 µg/ml respectively, while the ascorbic acid was IC 50 value of 11.24 and 6.83µg/ml by DPPH and nitric oxide scavenging assay. Many biological activities related to antioxidants are not evaluated yet, so this plant is a better option for those activities [18].…”
Section: Discussionmentioning
confidence: 99%
“…A brief summary of the phytochemistry of C. paniculatus is presented in Table 1, including different parts of plant, type of solvents, morphological activity, types of active constituents and medicinal uses (Gurumurthy et al, 2008; Kumar & Gupta, 2002; Mekari et al, 2009; Zohera et al, 2010).…”
Section: Phytochemistrymentioning
confidence: 99%
“…An investigation into possible toxic effects was conducted with polar and semi-polar compounds isolated from the fractionated seed oils in animal models. Upon injecting the fractionated extracts of seeds temporary adverse effects including fatty liver, degeneration of hepatic cells T A B L E 1 Morphological activity, active constituents and medicinal uses of various parts of C. paniculatus (Gurumurthy, Krishna, Patil, & Babu, 2008;Kumar & Gupta, 2002;Mekari, Patil, & Abilash, 2009;Zohera, Habib, Imam, Mazumdar, & Rana, 2010) and impairment of proximal tubular cells in the kidney were reported in rats (Bidwai, Wangoo, & Sharma, 1990).…”
Section: Central Nervous System Activitiesmentioning
confidence: 99%
“…[1][2][3] As the seeds were reported to possess significant antioxidant property, their protective effect against lead acetate induced nephrotoxicity has been investigated in this study by estimating biochemical, oxidative stress and antioxidant markers, histological and immunohistochemistry of KIM 1 expression. 4 The kidney is one of the most highly differentiated organs in the body that modulates a variety of physiologic processes especially the removal of drug metabolites. As per the Global Burden of Disease Study (2010), kidney diseases ranked 18 th in the list of causes of the total number of deaths worldwide that stood 27 th in 1990.…”
Section: Introductionmentioning
confidence: 99%